THE CHANGING CHARATER IN EDGAR ALLAN POE'S THE BLACK CAT - Mamahani, Serafim; Rorintulus, Olga A.; Andries, Fivy A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this research is to analyze how the changing character of the main character are revealed, the cause and the effect of the changing character on the main character. This research is categorized as qualitative research in which the data is in the form of words. The data collection is categorized by primary and secondary sources. The primary source is the short story itself, and the secondary sources are other books and references that used to support this research. The writer used an objective approach to analyze the data. This research shows that the main character endured a changing character. First, he is a good person. He is a docile person, human person and fond of animals. But he changed into a bad person. He grew, day by day, more moody, more irritable, more regardless of the feelings of others and he became a killer. The character changes of the main character give an effect on his wife and his pets. He not only hurt them, but he also killed them. The causes of his changing character are his alcoholism and his bad surroundings